2019
DOI: 10.1007/s00484-018-01658-x
|View full text |Cite
|
Sign up to set email alerts
|

Breeding birds actively modify the initial microclimate of occupied tree cavities

Abstract: The microclimate of cavities used by endothermic animals may depend on dynamic relationships between a cavity's physical properties and the heating activity of cavity users, but the rudiments of these relationships are unclear. I compared the temperature and relative humidity of active tree cavities that were occupied by nesting marsh tits Poecile palustris with the conditions in vacant tree cavities previously used for breeding by this species. I tested how presence of active nests modified initial cavity mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 51 publications
2
23
1
Order By: Relevance
“…However, we found similar differences between nest-types in both empty and occupied nests (Table A2). These results are in line with previous studies that found that even a much smaller bird, great tits Parus major , increased interior temperature and temperature buffering capacity in nest-boxes (Maziarz & Wesołowski, 2013; Vel’ký et al, 2010) as well as marsh tits Poecile palustris in natural cavities (Maziarz, 2019). Similarly to Maziarz 2019, and Maziarz and Wesołowski (2013), we found that humidity rates were lower in occupied compared to empty cavities (Table A2).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, we found similar differences between nest-types in both empty and occupied nests (Table A2). These results are in line with previous studies that found that even a much smaller bird, great tits Parus major , increased interior temperature and temperature buffering capacity in nest-boxes (Maziarz & Wesołowski, 2013; Vel’ký et al, 2010) as well as marsh tits Poecile palustris in natural cavities (Maziarz, 2019). Similarly to Maziarz 2019, and Maziarz and Wesołowski (2013), we found that humidity rates were lower in occupied compared to empty cavities (Table A2).…”
Section: Discussionsupporting
confidence: 92%
“…3): the presence of birds in the nest could buffer the humidity level to a medium level, in between the dry empty nest-boxes and the humid empty cavities. The effect of the presence of birds in the nest on microclimate underlines the greater energetic cost for birds using nest-boxes which showed greater microclimatic variations compared to natural cavities in our study site (Maziarz, 2019).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…We hypothesise that Myrmica ants are attracted to bird nests to exploit the heat generated by the hosts and/or the enhanced insulation properties of the nest structure, to raise their broods in more advantageous (warmer and stable) thermal conditions than in the ants' own nests. To test this hypothesis, we examine how the endothermic activity of birds modifies the thermal conditions of their nests in relation to the stage of the nesting cycle and/ or ambient temperatures, possibly affecting the amount of heat generated by the birds 16,17,31,32 . Next, we explore whether thermal ecosystem engineering by the wood warblers may have potential benefits for ants raising their broods within the birds' nests.…”
mentioning
confidence: 99%